Fabrication of dye natural as a photosensitizers in dye-sensitized solar cells (DSSC) - Hardani Hardani; Hendra Hendra; Muh. Iman Darmawan; C Cari; Agus Supriyanto (Journal of Physics: Theories and Applications, 2017)
The purpose of this study was to obtain optical properties (absorption spectrum) and electrical properties (photoconductivity) of organic dyes in DSSC performance. optical and electrical properties were tested by using UV-Visible Spectrophotometer and Elkahfi 1601 PC 100 / IV meter, respectively, while Keithley Type 2600A is used for the characterization of DSSC. This study is a great base to explore and investigate the development of DSSC solar cells using natural dyes (organic). Spectra optimal absorption and photoconductivity produced by natural dyes (organic). The results of this study indicate that the absorption spectrum of natural dyes (organic) in the range of 300-500 nm. electrical characteristics (I-V) of the increase in linear dye under illumination. I-V characteristics of DSSC from organically produced natural dyes to color the biggest-mangosteen obtained Voc of 565 mV; JSC = 1.52 A / m2; FF = 0.12; and η_ef is approximately 0.09%, respectively,. The conclusion of this study, natural dyes (organic) can be an attractive alternative as a dye.